Health Status of Marine and Freshwater Fish in Peru - Serrano-Martínez, Enrique (2023)
This study provides a historical overview of fishing and aquaculture in Peru, along with information on the current situation of these activities in terms of health, production, and regulations. The aim was to determine focus areas for generating new knowledge and innovation to boost the fisheries and aquaculture sectors, including the development of human capital and technology for the diagnosis of diseases in aquatic animals. It should be noted that the rainbowtrout (Oncorhynchus mykiss) and tilapia (Oreochromis niloticus) are the main fish species grown in fish farmsin Peru. However, there is only limited research regarding fish health, whether from fisheries or aquaculture.Furthermore, studies conducted on fish health are mostly isolated, resulting in insufficient evidence for decision-making, e.g., in relation to the development of fish health programs. The volumes of fishery resources extracted and of fish production from aquaculture demonstrate the need to strengthen research activities in these sectors. It is concluded that coordinated efforts involving the business sector (producers), government entities, and the academic sector are necessary to carry out studies to ultimately establish fish health programs and improve production and extraction systems for hydrobiological resources (fish) in Peru.